STUDY OF CAKES OF SOME MINING ENTERPRISES IN UZBEKISTAN - Usmonaliev Z. I.; Mirzakhmedov R.M; Anarbaeva Z. I.; Pulatova M. O.; Mirzoakhmedova S. A. (Scholars Digest Publishing, 2023)
The results of X-ray fluorescence and atomic emission analyzes of technogenic raw materials of mining production at MPZ AGMK JSC and GMZ No. 2 at NGMK JSC of the Republic of Uzbekistan are considered, which showed the content of non-ferrous metals such as gold, silver, copper, zinc, chromium, manganese and others.
Keywords: X-ray fluorescence analysis, atomic emission analysis, non-ferrous metals, industrial waste.